1989
DOI: 10.1159/000226739
|View full text |Cite
|
Sign up to set email alerts
|

In situ Detection of Epstein-Barr Virus Markers in Nasopharyngeal Carcinoma Patients

Abstract: Cryosections of nasopharyngeal tissue from 9 patients suspected of having nasopharyngeal carcinoma (NPC) were examined for the presence of Epstein-Barr virus (EBV) markers in situ to assess virus infection in the nasopharynx. Viral DNA, EB nuclear antigen, and/or early antigens (EA.D and EA.R) were detected in 5 NPC specimens. EBV infection was not confined to the tumor areas of the biopsy specimens. Lymphoid cells and nontumor areas of these specimens contained EBV markers. In addition, nasopharyngeal tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 8 publications
1
14
1
Order By: Relevance
“…In situ studies have shown the presence of EBV in car cinoma, and dysplastic epithelia of the nasopharynx [27,30,31], and occasionally in normal epithelium of NPC [9,31]. In this study, we were able to demonstrate EBER 1 in the squamous epithelia in NPC cases but not in the respi ratory epithelial cells.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In situ studies have shown the presence of EBV in car cinoma, and dysplastic epithelia of the nasopharynx [27,30,31], and occasionally in normal epithelium of NPC [9,31]. In this study, we were able to demonstrate EBER 1 in the squamous epithelia in NPC cases but not in the respi ratory epithelial cells.…”
Section: Discussionsupporting
confidence: 50%
“…Several studies have shown that EBV-harboring epithelial cells are occasionally present in the overlying mucosa of NPC [4,9], Little is known about persistent EBV infec tion in normal or nontumor nasopharyngeal mucosa and lymphoid cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have pointed out that human papillomavirus infection is associated with increased risk of oral cancer, independent of exposure to tobacco and alcohol (35,36). Therefore, up-regulations of ISGs, including IFIT2, at the tumor site could be caused by IFNs produced in response to ongoing viral replication in adjacent tissue, as reported for nasopharyngeal carcinoma patients with EBV infection (37). Whether the enhanced expression of IFIT2 in OSCC tissues is due to the inflammatory response to viral infection or chemicals warrants further investigations.…”
Section: Discussionmentioning
confidence: 93%
“…There is precedence for this in studies with varicella zoster that showed IFN production not in the infected cells per se but in the adjacent uninfected cells, thereby creating an antiviral state around the site of viral replication that functions to impede the spread of the virus to adjacent tissue (44). The up-regulation of ISGs at the tumor site could also be caused by IFNs produced in response to ongoing viral replication in tissue adjacent to the tumor (45). This would be consistent with serologic studies, which indicate that increasing levels of IgA antibodies to replicative antigens are diagnostic of NPC disease progression and relapse (46), although there is little viral replication in the tumor itself.…”
Section: Cancer Researchmentioning
confidence: 99%